Hubungan Tingkat Pengetahuan dengan Tingkat Stres dan Kecemasan Siswa Saat Vaksinasi Covid-19 - Ikha Rahardiantini; Cian Ibnu Sina (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2021)
The acute respiratory disease caused by the 2019 Novel Coronavirus (2019-nCoV) is officially named Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 causes the disease Coronavirus Disease 2019 (COVID-19). To overcome the spread of COVID-19, the government has imposed restrictions on residents' activities by enforcing the Large-Scale Social Restrictions (PSBB) regulations. This condition causes anxiety in the community. It is suspected that the level of knowledge will affect the level of stress and anxiety of middle and high school students. Aim. Knowing whether there is a relationship between the level of knowledge about COVID-19 with the stress and anxiety levels of junior and senior high school students during vaccination at the Poltekkes Kemenkes Tanjungpinang. Method. The method used is a cross sectional analytic approach with the use of the Slovin formula in determining the number of samples. The necessary data were obtained through a questionnaire during vaccination. This research took place from May to July 2021. Results. The research sample was obtained as many as 129 students. Based on the Spearman correlation test, the p value = 0.036, indicating a relationship between the level of knowledge and the level of perceived anxiety, as well as between the level of knowledge and the level of stress showed a relationship marked by the value of p = 0.040. Conclusion. There is a sufficient relationship between the level of knowledge about COVID-19 and the level of anxiety and stress during the PSBB period for junior high and high school students during vaccination at the Poltekes Kemenkes Tanjungpinang.The acute respiratory disease caused by the 2019 Novel Coronavirus (2019-nCoV) is officially named Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 causes the disease Coronavirus Disease 2019 (COVID-19). To overcome the spread of COVID-19, the government has imposed restrictions on residents' activities by enforcing the Large-Scale Social Restrictions (PSBB) regulations. This condition causes anxiety in the community. It is suspected that the level of knowledge will affect the level of stress and anxiety of middle and high school students. Aim. Knowing whether there is a relationship between the level of knowledge about COVID-19 with the stress and anxiety levels of junior and senior high school students during vaccination at the Poltekkes Kemenkes Tanjungpinang. Method. The method used is a cross sectional analytic approach with the use of the Slovin formula in determining the number of samples. The necessary data were obtained through a questionnaire during vaccination. This research took place from May to July 2021. Results. The research sample was obtained as many as 129 students. Based on the Spearman correlation test, the p value = 0.036, indicating a relationship between the level of knowledge and the level of perceived anxiety, as well as between the level of knowledge and the level of stress showed a relationship marked by the value of p = 0.040. Conclusion. There is a sufficient relationship between the level of knowledge about COVID-19 and the level of anxiety and stress during the PSBB period for junior high and high school students during vaccination at the Poltekes Kemenkes Tanjungpinang.